I'm going down with this ship understanding fandom and gender in the time of the internet - Porciuncula, Niña Liza Marie 1993- (2014)
"This research is about the implications of same-sex marriage shipping on the Filipino K-pop shippers' notions about gender. It follows David Gauntlett's argument that media has a significant but not straightforward relationship with our sense of gender and identity. in order to provide context, I sought to find out the shipping practices and motivations of Filipino shippers using Henry Jenkins' four levels of fan activity as a guide and by employing the Reflexive Dyadic Interview method. The motivations were classified under the categories of common reasons for media use by Denis McQuail and motivations for parasocial interaction by Gayle Stever. Other lenses were used for motivations that did not fit in these categories. After interpreting their practices and motivations. I found out that because the shippers - as Digital Natives - have access to the Internet where there is a proliferation of non-traditional gender images, they tend to be more open to ideas that transgress the mainstream notions of gender in the Filipino society. Shipping then becomes a negotiation between the normative culture and the shippers' non-traditional readings. Here, the shippers are seen as "queers" in the sense that they recognize gender fluidity and they are no longer bound by the traditional norms of the Filipino society."